2001
DOI: 10.1038/sj.onc.1204117
|View full text |Cite
|
Sign up to set email alerts
|

Smads mediate signaling of the TGFβ superfamily in normal keratinocytes but are lost during skin chemical carcinogenesis

Abstract: The Smads are the signaling mediators of the TGFb superfamily. In the present study, we examined Smad expression in mouse epidermis and chemically-induced skin tumors. Mutations in Smad2 and -4 genes were also screened. Transcripts of Smad1 through -5 were constantly expressed in the epidermis regardless of changes in TGFb signaling, state of dierentiation and stages of carcinogenesis. Smad7 transcripts were barely detectable in keratinocytes, but were induced by TGFb1 treatment and in chemically-induced skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 58 publications
10
57
0
Order By: Relevance
“…Our data indicated that Smad1-5 were expressed in all layers of the epidermis, including both the basal proliferative keratinocytes and suprabasal differentiated keratinocytes, whereas Smad6 and 7 were barely detectable in the epidermis (He et al, 2001). In the hair follicle, expression of Smad2 and 3 was quite weak, while Smad1, 4 and 5 were detected with intensities similar to those in the epidermis.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our data indicated that Smad1-5 were expressed in all layers of the epidermis, including both the basal proliferative keratinocytes and suprabasal differentiated keratinocytes, whereas Smad6 and 7 were barely detectable in the epidermis (He et al, 2001). In the hair follicle, expression of Smad2 and 3 was quite weak, while Smad1, 4 and 5 were detected with intensities similar to those in the epidermis.…”
Section: Introductionmentioning
confidence: 72%
“…It is known Smad4 interacts with Smad1, 5 and 8 to mediate BMP signaling, and with Smad2 and 3 to mediate signaling of TGFb subfamily members, while BMPR1A only mediates signals of BMP subfamily (Heldin et al, 1997;Massague, 1998;ten Dijke and Hill, 2004). We have shown previously that all these Smads, except for Smad8, whose expression in skin has not been studied, are expressed in hair follicles and epidermis (He et al, 2001). Thus, it is plausible that the increased cell proliferation in the epidermis and ORS of the hair follicle is largely due to a block of signals of the TGFb subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that TGF-␤-induced growth inhibition in epithelial cells is preferentially mediated by Smad3 (10,11) and that cyclin-dependent kinase (cdk) 2 and cdk4 can phosphorylate Smad3, thus inactivating its ability to instigate cell cycle arrest (12). Therefore, Smad3 may mediate TGF-␤1-induced growth inhibition during cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…12,17,18 Furthermore, in chemically induced murine epidermal tumors and in human basal cell carcinoma cells, Smad1/5 are strongly down-regulated. 19 Skin-specific disruption of Smad4 results in increased epidermal proliferation consequently leading to squamous cell carcinoma formation. 20,21 Antitumor activity of BMPs may also be regulated by extracellular BMP inhibitors: expression of the BMP antagonist gremlin increased in basal cell carcinomas, in which gremlin promotes and BMPs inhibit cell proliferation.…”
mentioning
confidence: 99%